Slangs of the city of São Paulo and the use of obscene vocabulary in song lyrics - Valadares, Flávio Biasutti; Lobo, Raphael Leandro (Entrepalavras, 2025)
This paper analyses slangs of the city of São Paulo, particularly its use as obscene vocabulary in song lyrics, and aims to create a semantic-pragmatic language framework from a variationist perspective. This study is grounded in Variationist Sociolinguistics and Pragmatics. Data have been primarily selected from the city of São Paulo funk music lyrics over the past decade, including at least two songs from each geographic region of the city and two songs from each year between 2016 and 2023. Additionally, this research establishes a categorization analysis framework to classify obscene vocabulary based on the corpus used. In conclusion, the data reveal a trend in the use of obscene vocabulary in a diverse, creative and subversive way, often highlighting the ambiguity and polysemy of the words chosen by the São Paulo city funk/batidão artists.